The relevance of non-legal technical and scientific concepts in the interpretation and application of the law of the sea - Guy N R (Institute of Marine and Environmental Law, 2025)
Of necessity LOSC Articles are brief and in some instances vague and requiring interpretation. There is general consensus that LOSC is successful and that its vagueness in certain areas is an asset allowing a variety of otherwise contrary attitudes to be accommodated. It is necessary to analyse the Articles with a view to a better understanding of them and to possibly prepare for some future conference or convention that will more than likely be necessary to resolve some of the remaining problems. To illustrate the need for greater understanding of some of the Articles of LOSC the United Nations Office for Ocean Affairs and Law of the Sea found it necessary to convene a conference of 'experts' during 1993 and 1995 to consider the implications of the complex Articles of LOSC which deal with claims to the continental shelf. Criteria contained in Article 76 allowing for maximum outer limits of the continental shelf and other criteria to justify a claim are complicated and require experience in many fields including marine geology, geography, surveying, and geodesy. The intention is therefore to analyse the possible interpretation, application and consequences of the implementation of Articles in LOSC, and more particularly in a Southern African context. Provisions of LOSC, where technical and scientific considerations are crucial, will be selected for consideration. These include those involving geodetic, geographical, geological, survey, navigational, organisational, and social and resource factors. The effect of these factors on LOSC will be assessed and interpreted and any shortcomings found in the Articles will be highlighted and suggestions made for their possible improvement or interpretation.